Factors Associated with Baby Blues Syndrome in Post Partum Mothers in Daya Hospital Makassar City - Kasim, Erna (ScieClouds Publishing, 2023)
The incidence of post partum blues quite high at 26.00% -85.00%. Of the several studies described as much as 50.00% of mothers after childbirth are depressed and almost 80.00% of new mothers experience postpartum blues, or often called Post Partum Blues. 50-70% of all postpartum women will experience this syndrome. The research objective was to determine the factors associated with the syndrome baby blues on post partum mothers in hospitals Power Makassar. The research method is analytical, using cross sectional design. The study population was all normal post partum patients in hospitals Power Makassar. Samples numbered 32 people using accidental sampling technique. Data were collected by questionnaires and then conducted a statistical analysis using chi square test with alternative test Fisher's exact test with a significance level a < 0,05. The results based on age shows that most mothers are at an age not at risk as many as 24 people (75, 0%). Based on parity, most are not at risk as many as 24 people (75, 0%). Based on the support of her husband, most mothers received support as many as 26 people (81.2%). Based on the knowledge, most mothers with a good knowledge of as many as 23 people (71.9%). While based on the incidence of the syndrome baby blues most mothers do not experience the baby blues syndrome as many as 23 people (71.9%). Based on the results of the study concluded that there is a relationship between maternal age, maternal parity, husband's support, and knowledge with baby syndrome in mothers postpartum blues. Suggested to the public / patient in the presence of this study can add to the information and knowledge about the syndrome baby blues so as to prevent the baby blues.